2016
DOI: 10.4149/neo_2016_514
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoints in aggressive breast cancer subtypes

Abstract: Immune checkpoints are molecules referred to inhibitory pathways in the immune system that play a pivotal role in prevention of autoimmunity and oncogenesis. The aim of the study was to evaluate expression levels of selected immune checkpoints- PD-1 (programmed cell death protein 1), and PD-L1 (programmed cell death 1 ligand 1) in breast cancer patients, suitable for breast conservation and sentinel node biopsy and determine their associations with clinicopathological factors.Expression of the genes coding for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…In addition, it has been reported that PD‐L1 is differentially expressed across different BC subtypes. In particular, available evidence consistently reports greater expression of PD‐L1 in the TN subtype (up to 60% of PD‐L1 expression) compared with non‐TNBC . These data appear to be coherent with the observation that PD‐L1 tumor expression is positively associated with stromal tumor‐infiltrating lymphocytes (TILs) in this BC subtype , which is known to be more frequently infiltrated by stromal TILs than non‐TNBC , as summarized in Table , thus possibly suggesting that these two immune biomarkers tend to run parallel.…”
Section: Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…In addition, it has been reported that PD‐L1 is differentially expressed across different BC subtypes. In particular, available evidence consistently reports greater expression of PD‐L1 in the TN subtype (up to 60% of PD‐L1 expression) compared with non‐TNBC . These data appear to be coherent with the observation that PD‐L1 tumor expression is positively associated with stromal tumor‐infiltrating lymphocytes (TILs) in this BC subtype , which is known to be more frequently infiltrated by stromal TILs than non‐TNBC , as summarized in Table , thus possibly suggesting that these two immune biomarkers tend to run parallel.…”
Section: Methodssupporting
confidence: 74%
“…Data on PD‐L1 expression in HER2‐positive BC are more controversial. In fact, whereas in some studies HER2 positivity has been correlated with higher expression of PD‐L1 (up to 50%) compared with HER2‐negative BC , others failed to report any difference .…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Our current results further showed that loss of PIPKIγ suppressed the expression of PD-L1, which likely also contributes to the inhibition of cancer progression caused by PIPKIγ depletion, because loss of PD-L1 expression makes tumor cells much less defensive to anti-tumor immunity. Additionally, recent studies suggested a correlation between PD-L1 and the epithelial-to-mesenchymal transition (EMT) in solid tumors to regulate cancer metastasis [50, 5154]. The pro-metastatic process EMT may induce breast cancer PD-L1 expression and immune suppression in a PI3K/AKT and/or MEK/ERK dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…51 Higher PD-1 and PD-L1 RNA levels were seen in TNBC and HER-2 C tumors compared with luminal A and luminal B HER-2 ¡ tumors; expression levels increased with tumor grade suggesting increasing immune suppression with disease progression. 52 Studies are currently ongoing to evaluate anti-PD-1 and anti-PD-L1 antibodies in metastatic BC.…”
Section: Pd-1mentioning
confidence: 99%